The possibilities of wide-range MSCT in assessing the invasion of mediastinal structures in giant neoplasms of the thoracic organs - Irina M. Koroleva; Vladimir D. Parshin; Elvira Z. Mukhamatullina; Maria A. Mishchenko (ZAO "Consilium Medicum", 2022)
Despite the constant increase in the level of equipment of medical institutions with modern high-tech equipment (CT, MRI, endoscopes, etc.), in the last decade there has been a clear trend towards an increase in the number of patients with tumors of intra-thoracic localization, including giant sizes. Oncologists consider neoplasms that occupy more than half of the hemithorax or simultaneously spread to the anterior and posterior mediastinum to be giant tumors of the chest. According to leading oncologists, giant tumors should include chest tumors whose diameter is equal to or exceeds 20 cm, have different initial localization, more than 80% of cases have different histological affiliation. There is no unity of views of leading oncologists and thoracic surgeons on the classification of giant intra-thoracic formations, diagnosis, determination of their initial localization and, accordingly, determination of the possibility of their surgical treatment and selection of optimal access. It is not uncommon when issues related to the initial localization, histological affiliation, as well as invasion of surrounding structures are resolved during surgical intervention. Unfortunately, there is little information in the Russian scientific literature about the high-tech diagnosis of this group of neoplasms, then malignant formations are twice as common as benign ones. Given the prevalence of malignant neoplasms in the category of giant tumors of intra-thoracic localization, a very relevant diagnostic issue is the identification of invasion of mediastinal structures, which largely determines both the feasibility of surgical intervention and its possible variants.